Rural–urban differences in suicide attempts and mortality among young people in northern Sweden, 1998–2017: A register-based study. Issue 8 (December 2020) - San Sebastián, Miguel; Edin-Liljegren, Anette; Jonsson, Frida
Aim: The aim of this study was to assess trends in suicide attempts and mortality between 1998 and 2017 by residential area and gender among northern Swedish youths. Methods: Events of suicide attempts and deaths for each municipality in the four counties of the northern Swedish region, stratified by gender, were retrieved for each year from 1998 to 2017. All cases identified within the registers with the diagnostic codes X60–X84 or Y10–Y34 (International Classification of Diseases, 10th revision) for individuals aged 15–24 years were included. Place of residence at municipal level was categorized into three groups: rural – municipalities with a population of <10, 000 inhabitants; semi-rural – those between 10, 000 and 50, 000; and urban – those with >50, 000 inhabitants. Results: The rates of attempted suicides in the northern region were higher in both men and women than in Sweden, while the rates of suicide deaths were slightly higher in young men but similar in young women compared to the national averages. Overall, the risk of suicide attempts was higher in semi-rural municipalities compared to urban ones, particularly among women. A significantly higher risk of mortality was also observed for men and women in semi-rural municipalities, but only in the period 2010–2013. Conclusions: The high rates of attempted and completed suicides among youth in northern Sweden and the higher risks in rural and semi-rural municipalities need close attention. The implementation of suicide prevention programs, especially in rural and semi-rural municipalities, should be intensified.